Risk-Based Business Continuity Strategy for a Newspaper Printing Company: a Qualitative Case Study - Khansa Aida Dewiyanti; Ana Noveria (Universitas Pahlawan Tuanku Tambusai, 2026)
The continuing decline of the print media industry has caused increasing pressure on newspaper printing companies and threatens their long-term business continuity. PT Mediacetak, a newspaper printing company that still heavily dependent on a single internal client and operates with single-unit production equipment, has no formal risk management system and is therefore vulnerable to both internal and external risks. This study aims to identify the company's key business risks, assess their likelihood and impact, and develop mitigation strategies that support its business continuity. This study adopts the ISO 31000:2018 framework using a qualitative single-case study approach. Primary data were collected through semi-structured interviews with five key respondents and a risk scoring questionnaire completed by six employees across functional areas. Interview data were analysed using deductive thematic analysis, while risk levels were determined by multiplying the average likelihood and impact scores. The findings identified 23 risks across six categories, which are strategic, operational, financial, supply chain, human resource, and external and technology risks, of which 13 were classified as priority risks. Treatment strategies were developed for all priority risks, including preventive maintenance, backup supplier arrangements, pricing adjustment mechanisms, and business diversification. Residual risk analysis indicates that the proposed treatments reduced most priority risks to the Moderate level, although several strategic and external risks remained at higher levels because they are driven by factors beyond the company's control. The study concludes that while operational risks can be managed through internal improvements, the company's long-term business continuity depends heavily on successful diversification beyond newspaper printing.